PENGARUH STRUKTUR KEPEMILIKAN INSTITUSIONAL, KOMISARIS INDEPENDEN DAN KESEMPATAN INVESTASI TERHADAP STRUKTUR MODAL DENGAN RATING OBLIGASI SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Sektor Non Keuangan yang Terdaftar di BEI) - Agnesya, Luvita; Haryetti, Haryetti; Fathoni, Akhmad Fauzan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
In achieving the company’s goals then the necessary planning. For large companies usually not only from own property but also from investors. In managing the capital required a strategy to determine the optimal capital structure for the company to achieve its goals. This study aimed to determinethe effectsof institutional ownership structure, Indepedentdirectors and investment opportunity on capital structure with bond rating as moderating variable. The population in this study is non financial firms in Indonesia Stock Exchange for period 2012-2015. This studi has population as many as 439 firms of non financial firms in Indonesia Stock Exchange. Samples were 38 non financial firms. This study used purposive sampling method and moderated regression analysis as analysis method. The result show that the institutional ownership structure has negatif influence but not significant to the capital structure and outsidedirectors did not have significant effect to the capital structure. Investment pportunity set has negative significant effect to the capital structure. Bond rating has negative significant influence in relation between institutional ownership structure and capital structure. But, bond rating did not have significant influence in relation between outside directors and capital structure as well as relation between investment opportunity and capital structure.Keywords: Capital Structure, Institutional Ownership Structure, Outside Directors, Investment Opportunity and Bond Rating.